Risk factors of the thyroid cancer - Miśkiewicz, Joanna; Ciuła, Aleksandra; Jakubiak, Anna; Karaban, Łukasz; Paszkowska, Monika; Borawski, Michał; Mularczyk, Klaudia; Znamirowska, Patrycja; Kuźnieców, Tadeusz; Kupis, Magdalena (Quality in Sport, 2025)
Introduction and purpose: These days, thyroid cancer (TC) is the most common endocrine cancer. According to , Cancer in Poland in 2022” thyroid cancer affected 47800 women in 2022. A better understanding of the illness will help develop more potent treatment and prevention strategies. The goal of our work is to classify and describe risk factors [RF] for TC. Review Methods: A systematic search of the ‘’PubMed’’ database was conducted, focusing on studies published within the last 10 years. The search strategy used relevant key words related to TC and RF. Studies were included if they provided information on RF associated with TC in the adult population. The articles that are most relevant to the topic have been selected. State of knowledge: It is known that TC has several RF. According to recent research, female sex, radiation, low physical activity, obesity, metabolic syndromes and lifestyle choices are the most significant RF. Other elements that raise the chance of TC include, for example family history of thyroid cancer, iodine deficiency, inadequate sleep, hormonal and genetic factors, eating meals high in sugar. Adequate physical activity, getting enough good sleep, eating dairy products, oranges and persimmons and a healthy lifestyle are associated with a lower risk of thyroid cancer; nevertheless, smoking and drinking alcohol, also reduces the disease’s likelihood. Summary: Many medical, genetic, and environmental factors are believed to be linked to a higher risk of TC. Research into RF for the disease could be useful in the development of prevention facilitating the application of suitable screening programs, diagnostic and treatment techniques. Further study is required to fully understand the etiopathology of TC, identify all RF, and verify whether they can be used for the procedure of treatment, as they are not well enough recognized.